Collective labor supply heterogeneity and nonparticipation - Richard W. Blundell; Pierre-Andre Chiappori; Thierry Magnac; Costas Meghir (Institute for Fiscal Studies (IFS), 2001)
We present identification and estimation results for the “collective” model of labour supply in which there are discrete choices, censoring of hours and nonparticipation in employment. We derive the collective restrictions on labour supply functions and contrast them with restrictions implied by the usual “unitary” framework. Using the large changes in the wage structure between men and women in the UK over the last two decades we estimate a collective labor supply model for married couples without children. The implications of the unitary framework are rejected while those of the collective approach are not. The estimates of the sharing rule show that wages have a strong influence on bargaining power within couples.
Keywords: 330; Arbeitsangebot; Haushaltsökonomik; Familienökonomik; Geschlecht; Theorie